Laser irradiation and thermal treatment inducing selective crystallization in Sb2O3-Sb2S3 glassy films - Avila, L. F.; Pradel, A.; Ribeiro, Sidney José Lima [UNESP]; Messaddeq, Younes [UNESP]; Nalin, Marcelo [UNESP] (My University, 2015)
The influence of both thermal treatment and laser irradiation on the structural and optical properties of films in the Sb 2 O 3 –Sb 2 S 3 system was investigated. The films were prepared by RF-sputtering using glass compositions as raw materials. Irreversible photodarkening effect was observed after exposure the films to a 458nm solid state laser. It is shown, for the first time, the use of holographic technique to measure “in situ”, simultaneously and independently, the phase and amplitude modulations in glassy films. The films were also photo-crystallized and analysed “in situ” using a laser coupled to a micro-Raman equipment. Results showed that Sb 2 S 3 crystalline phase was obtained after irradiation. The effect of thermal annealing on the structure of the films was carried out. Different from the result obtained by irradiation, thermal annealing induces the crystallization of the Sb 2 O 3 phase. Photo and thermal induced effects on films were studied using UV–Vis and Raman spectroscopy, atomic force microscopy (AFM), thermal analysis (DSC), X-ray diffraction, scanning electron microscopy (MEV) and energy-dispersive X-ray spectroscopy (EDX).